The Correlation between Happiness and Self-transcendence in the Elderly of Khoshkrud, Zarandieh City - M Lalehkani; A Davati; A Isanejad; M Jadid-Milani (Iran University of Medical Sciences, 2020)
Background & Aims: The population of the elderly has been on a rise, which shows more attention to ensuring the health and well-being of the elderly. On the other hand, the growth of the elderly population and its impact on the social and economic conditions of society leads to more attention to the issue of aging in society. In addition, physical and psychological abilities decrease with aging, which affects the quality of life of people. Overall, quality of life and well-being assessed by indicators such as health, happiness, and loneliness. Happiness is one of the most important needs of human beings, which considerably affects their psychological and physical health that helping the elderly cope with stressful situations. Another factor affecting well-being is self-transcendence, which is a powerful coping mechanism and can lead to personal transformation and improvement of the quality of life, thereby facilitating the process of understanding life changes such as aging. Therefore, self-transcendence is defined as a positive trait in relation to the expansion of one's outlook on life. This issue includes factors such as spirituality, finding a purpose in life, optimism for the future, coping with problems, using power-based approaches, and connecting with others. In the elderly, by restoring the concept of aging and accepting disability, it reduces stress and focuses more on ability than disability. Therefore, happiness and self-transcendence are important factors in the elderly's health dimensions. The present study aimed to determine the relationship between happiness and self-transcendence in the elderly of Khoshkrud, Zarandieh City. Materials & Methods: This descriptive-correlational research performed on the elderly selected from those who referred to the health center to receive elderly-related care using sequential sampling. Data collection continued for three months (October-December, 2019), and 84 elderlies who were willing to participate in the research were selected. The inclusion criteria were the age of more than 60 years, the ability to respond to questions physically and mentally, having psychological health  which assessed  by Abbreviated Mental Test (obtaining a score above 7) and not losing a family member or experiencing a stressful situation in the past two months. Abbreviated Mental Test used to diagnose cognitive impairment, including dementia and delirium in the elderly, applied to assess concentration, attention, short-term and long-term memory. Notably, the Cronbach's alpha of the tool was 0.76 in Iranian society. The Oxford Happiness Index has 29 questions that scored in a range of zero to 87 and includes five components of life satisfaction, self-honor, subjective well-being, satisfaction, and positive mood. Internal consistency was used to determine the reliability of the instrument. The Cronbachchr('39')s alpha coefficient for the components of life satisfaction, self-honor, subjective well-being, satisfaction, and positive mood estimated at 0.85, 0.71, 0.74, 0.79, and 0.77, respectively. On the other hand, the self-transcendence questionnaire included 15 items scored in a range of 15-60, where a higher score was indicative of higher self-transcendence. Internal consistency was used to determine the reliability of the instrument and its Cronbachchr('39')s alpha coefficient estimated to be 0.69. Researcher with questions from the elderly completed all tools and it took an average of 45 minutes for each elderly person to complete the tools. In addition, data analysis was performed in SPSS version 16 using descriptive statistics (to describe demographic variables and variables of happiness and self-transcendence) and parametric inferential statistics (Pearson's correlation coefficient, independent t-test, and analysis of variance). Results: In this study, the mean age of the elderly was 65.7±4.8 (60, 79). Moreover, 55 subjects were female (65.5%), 81% were married, 59.5% were illiterate and 64.3% were homemakers. In addition, the mean number of children of the participants was 6.2±1.6 (0, 14). Furthermore, 66.7% had an underlying illness, 56% had a moderate economic status, 61.9% had a family support system and 79.8% lived with their spouse. According to the results, the mean of happiness and self-transcendence in the elderly were 54.42±14.3 and 39.4±5.9, respectively. There was a significant and direct relationship between self-transcendence and happiness (r=0.263, P=0.016), components of life satisfaction (r=0.348, P=0.001) and satisfaction (r=0.325, P=0.003). In addition, a significant difference was observed between the level of education (P=0.038 and P=0.009, respectively) with happiness and self-transcendence and between occupational status and happiness (P=0.039). Moreover, a significant difference was found between the number of children (P=0.037) and residential status (P=0.028) with self-transcendence. Conclusion: According to the results of the study, happiness and its components were more than the average level in the elderlies. In addition, the results were indicative that level of education, job, and economic status had significant differences with happiness. A proper education, job and economic status creates safety in the individual, which improves happiness. Self-transcendence was moderate and economic status, level of education, residential status and number of children had significant differences with elderly's self-transcendence. Good economic situation causes security in the person and the person can try to help himself without worry and play a role in promoting self-transcendence. On the other hand, the level of education promotes awareness and the ability to obtain information from various sources, which can empower the elderly in self-care and increase their adaptation to old age, and ultimately lead to the promotion of self-transcendence. The presence of children, their support, and care for parents cause security for the elderly, who in return try to adapt to the current situation in order to calm their children and accept their situation and ultimately improve their self-transcendence. In general, self-transcendence promoted by having a good friend and a person to talk to, and in the traditional society of Khoshkroud, communication with children, relatives, and neighbors can promote self-transcendence. Although in the present study, the economic situation was moderate and most of the elderly were illiterate, the level of happiness and self-transcendence of the participants was above average, which can be attributed to the existence of social relations at the family and traditional society and respect for the elderly. These factors played a key role in individual satisfaction and support of the elderly and covered the educational and economic states. Moreover, there was a direct and significant relationship between happiness and self-transcendence. Happy people feel more in control, think more about their abilities rather than inabilities, better cope with life stressors, have higher self-esteem, value themselves, and love themselves. Overall, happiness can affect the scope of life and the way people relate and interact with the environment. As such, happiness promotes other life aspects, including self-transcendence. In Khoshkroud, where the elderly and families adhere to their religious and traditional beliefs and the family has a special position, the elderly enjoy health in all dimensions, and they can accept the conditions of old age and use effective adaptation mechanisms to improve well-being. It recommend that the families and authorities by meeting the economic, social and spiritual needs of the elderly to increase their ability to understand and accept themselves, create a sense of satisfaction and happiness, which increases their health. By creating a happy and lively environment, their performance will be improve, which has positive consequences for the elderly, family, and society. Furthermore, conditions should be provided for them to benefit from each otherchr('39')s experiences and to be present in public to improve their health.